Mulberry (Morus alba L.) Fruit Extract Ameliorates Inflammation via Regulating MicroRNA-21/132/143 Expression and Increases the Skeletal Muscle Mitochondrial Content and AMPK/SIRT Activities - Sunyoon Jung; Mak-Soon Lee; Eugene Chang; Chong-Tai Kim; Yangha Kim (MDPI AG, 2021)
The Mulberry (Morus alba L.) fruit is a rich source of polyphenolic compounds; most of these are anthocyanins. Obesity is intimately related to low-grade inflammation, with increased pro-inflammatory cytokine secretion and macrophage infiltration in white adipose tissue (WAT). This study investigated whether mulberry fruit extract (ME) has beneficial effects on obesity-induced inflammation and skeletal muscle mitochondrial dysfunction. Sprague-Dawley rats were divided into four groups and fed either a low-fat diet (LFD), high-fat diet (HFD), HFD + 5 g/kg of ME (ME-L), or HFD + 10 g/kg of ME (ME-H) for 14 weeks. ME alleviated dyslipidemia and lipid accumulation, as well as pro-inflammatory cytokine production such as tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6), and monocyte chemoattractant protein 1 (MCP1) in the WAT. ME mitigated nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) phosphorylation and macrophage infiltration in WAT. Notably, microRNA (miR)-21, miR-132, and miR-43 expressions were downregulated in the WAT of the ME groups compared to the HFD group. Moreover, ME increased the mitochondrial size and mitochondrial DNA (mtDNA) content, as well as key genes' expression related to mitochondrial function, including sirtuin (SIRT)1, peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α), carnitine palmitoyltransferase 1β (CPT-1β), and uncoupling protein 3 (UCP3), and adenosine monophosphate-activated protein kinase (AMPK)/SIRT activities in skeletal muscle. These results suggested that ME might alleviate obesity-induced inflammation and mitochondrial dysfunction by regulating miR-21, miR-132, and miR-43 expression in WAT, and by activating the PGC-1α/SIRT1 pathway in muscle.